2013
DOI: 10.1007/s00436-013-3597-7
|View full text |Cite
|
Sign up to set email alerts
|

Screening of plant extracts for anthelmintic activity against Dactylogyrus intermedius (Monogenea) in goldfish (Carassius auratus)

Abstract: With the aim of finding natural anthelmintic agents against Dactylogyrus intermedius (Monogenea) in goldfish (Carassius auratus), 26 plants were screened for antiparasitic properties using in vivo anthelmintic efficacy assay. The results showed that Caesalpinia sappan, Lysima chiachristinae, Cuscuta chinensis, Artemisia argyi, and Eupatorium fortunei were found to have 100% anthelmintic efficacy at 125, 150, 225, 300, and 500 mg L(-1) after 48 h of exposure. Crude extract of the five plants were further partit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 20 publications
0
20
0
2
Order By: Relevance
“…Wang et al (2010a) found that the efficacy of steroidal saponins from Dioscorea zingiberensis was up to 90% and Wang et al (2011) found that osthol extract from Radix angelicae pubescentis had efficacy of 100%. On the other hand, Huang et al (2013) reported that ethyl acetate extract from Lysima chiachristinae presented 50% efficacy against D. intermedius.…”
Section: Discussionmentioning
confidence: 95%
“…Wang et al (2010a) found that the efficacy of steroidal saponins from Dioscorea zingiberensis was up to 90% and Wang et al (2011) found that osthol extract from Radix angelicae pubescentis had efficacy of 100%. On the other hand, Huang et al (2013) reported that ethyl acetate extract from Lysima chiachristinae presented 50% efficacy against D. intermedius.…”
Section: Discussionmentioning
confidence: 95%
“…Hashimoto et al (2016) also found low efficacy (1.9%) for 20 mg/L of the essential oil of L. sidoides against monogenoideans of Nile tilapia. On the other hand, exposure of C. auratus to extracts of Cinnamomum cassia, Lindera aggregata, Pseudolarix kaempferi, Caesalpinia sappan, Lysima chiachristinae, Cuscuta chinensis, Artemisia argyi and Eupatorium fortunei showed 100% efficacy against Dactylogyrus intermedius (Huang et al, 2013;Ji et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the chemical products involved cause death among fish because of their toxicity (Boijink et al, 2015;Steverding et al, 2005;Zhang et al, 2013;Zhang et al, 2014). Thus, many researchers' attention has been drawn towards seeking natural antiparasitic products (Boijink et al, 2015;Hashimoto et al, 2016;Huang et al, 2013;Ji et al, 2012;Steverding et al, 2005;Xiao-Feng et al, 2014;Zhang et al, 2013;Zhang et al, 2014;Zheng et al, 2015), since these could form an alternative to chemotherapeutic products.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations